BIOLUMINESCENT ORGANISMS (Academicia Globe: Inderscience Research, 2022)
According to some studies, bioluminescence systems are virtually unexplored. Of the at least forty different bioluminescence systems believed to exist in nature, only seven are known to have molecular components of the light-emitting reaction, and the complete biochemical pathway leading to light emission is understood for only two of them. Luciferases include a group of enzymes that emit light in the presence of oxygen and a substrate (luciferin). Such a luciferin-luciferase system is found in nature, for example, in bacteria (Vibrio harveyi), dinoflagellates (Gonycaulax), and bile ducts (Photinus pyralis).